Peningkatan Kemampuan Representasi Matematis Siswa Sekolah Dasar melalui Pembelajaran Berbasis Proyek dengan Memanfaatkan Limbah Organik - Novianti Novianti; Shaila Safira; Shelly Devi Yanti; Faizaturrahmi Faizaturrahmi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Mathematical representation skills are one of the essential competencies that elementary school students need to have. However, there are still many students who experience learning obstacles in connecting mathematical concepts with the context of daily life. This is due to the abstract nature of mathematics, making it difficult for students to convey mathematical ideas in a representative manner. This research aims to improve students' mathematical representation skills through project-based learning by utilizing inorganic waste as a learning medium. This study uses a pre-experimental method with a one group pretest-posttest design. The research activity was carried out at UPTD SD Negeri 18 Juli by involving 25 grade III students as research subjects. Data collection is carried out through observation, initial tests, and final tests, while discussion activities are facilitated through Student Worksheets (LKS). The research instrument is in the form of description questions that contain indicators of mathematical representation ability. The results showed a significant increase in the three aspects of mathematical representation, namely the visual (from a score of 4.5 to 7.6), the symbolic (from 4.3 to 8.0), and the verbal (from 5.0 to 8.3). Thus, it can be concluded that project-based learning by utilizing inorganic waste is effective in improving the mathematical representation skills of elementary school students. In addition, this approach also fosters environmental awareness and students' creativity in recycling waste into products with useful value.